Cooperative Development in the South China Sea: : Policies, Obstacles, and Prospects - Qi, Huaigao; Xue, Song; Qi, Huaigao; Xue, Song (Taylor & Francis, 2020)
"Boundary disputes in the South China Sea have been a long- standing threat to peace and security in East and Southeast Asia. Without agreed defi nition of boundaries, provisional arrangements to develop resources in the disputed area have become the favored, and most effective, solution. Therefore, joint development between various countries has taken place in the form of ad hoc arrangements with the goal of achieving positive outcomes for all parties involved. Incorporating insights from ten authors from six countries (Brunei, China, Indonesia, Malaysia, the Philippines, and Vietnam), this book provides a comprehensive analysis of the incentives and policies for joint development in the South China Sea disputes. The authors also discuss the bottlenecks and proposed policy options. The authors ease doubts over joint development in South China Sea disputes and shed light on creative ways to promote cooperation. The book is a key reference for students and scholars in politics and international relations, Asian studies, and maritime law."
English
Keywords: Politics & government; International relations; international cooperation; South China Sea